MicroRNA dysregulation in myelodysplastic syndromes: implications for diagnosis, prognosis, and therapeutic response - Micheva, Ilina Dimitrova; Atanasova, Svilena Angelova (Frontiers in Oncology, 2024)
Myelodysplastic syndromes (MDS) are a group of malignant clonal hematological disorders with heterogeneous clinical course and risk of transformation to acute myeloid leukemia. Genetic and epigenetic dysregulation, including alterations in microRNA (miRNA) expression, plays a pivotal role in MDS pathogenesis influencing disease development and progression. MiRNAs, known for their regulatory roles in gene expression, have emerged as promising biomarkers in various malignant diseases. This review aims to explore the diagnostic and prognostic roles of miRNAs in MDS. We discuss research efforts aimed at understanding the clinical utility of miRNAs in MDS management. MiRNA dysregulation is linked to specific chromosomal abnormalities in MDS, providing insights into the molecular landscape of the disease. Circulating miRNAs in plasma offer a less invasive avenue for diagnostic and prognostic assessment, with distinct miRNA profiles identified in MDS patients. Additionally, we discuss investigations concerning the role of miRNAs as markers for treatment response to hypomethylating and immunomodulating agents, which could lead to improved treatment decision-making and monitoring. Despite significant progress, further research in larger patient cohorts is needed to fully elucidate the role of miRNAs in MDS pathogenesis and refine personalized approaches to patient care.